Konseling Kelompok Active Music Therapy Berbasis Cognitive Behavior Therapy (CBT) untuk Meningkatkan Self-Efficacy Mahasiswa Millennials - Dominikus David Biondi Situmorang; Mungin Eddy Wibowo; Mulawarman Mulawarman (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2018)
Abstract: This research is a new breakthrough in Indonesia, which integrates the approach of Cognitive Behavior Therapy (CBT) - as a conventional counseling approach with music therapy as expressive techniques in counseling. The aim of this study is to determine the effectiveness of group counseling service implementation of CBT with active music therapy technique to improving self-efficacy of millennials students. This study used quasi-experimental design (pretest, posttest, and follow-up). Group counseling was conducted for 5 meetings (each meeting was 100 minutes), and follow-up was performed after 2 weeks of treatment. Subject selection using purposive sampling technique that is based on inclusion criteria and level of self-efficacy obtained from self-efficacy scale. The results of this research showed that group counseling of CBT with active music therapy technique was significantly effective in improving self-efficacy of millennials students at pretest vs. posttest, pretest vs. follow-up, and posttest vs. follow-up.Abstrak: Penelitian ini merupakan terobosan baru di Indonesia yang mengintegrasikan pendekatan Cognitive Behavior Therapy (CBT) - sebagai pendekatan konseling konvensional dengan music therapy sebagai expressive techniques in counseling. Tujuan penelitian ini ialah untuk mengetahui efektivitas konseling kelompok CBT dengan teknik active music therapy untuk meningkatkan self-efficacy mahasiswa millennials penyusun skripsi. Penelitian ini menggunakan desain quasi-eksperimental (pretest, posttest, dan follow-up). Konseling kelompok dilaksanakan selama 5 pertemuan (tiap pertemuan 100 menit), dan follow-up dilakukan setelah 2 minggu diberikan treatment. Pemilihan subjek menggunakan teknik purposive sampling didasarkan pada kriteria inklusi dan tingkat self-efficacy yang diperoleh dari self-efficacy scale. Hasil penelitian menunjukkan bahwa konseling kelompok pendekatan CBT dengan teknik active music therapy secara signifikan efektif untuk meningkatkan self-efficacy mahasiswa millennials pada saat pretest vs. posttest, pretest vs. follow-up, dan posttest vs. follow-up.